2010
DOI: 10.1200/jco.2009.24.8872
|View full text |Cite
|
Sign up to set email alerts
|

Phase II, Randomized, Open-Label Study of Pegfilgrastim-Supported VDC/IE Chemotherapy in Pediatric Sarcoma Patients

Abstract: This multicenter, randomized, open-label study evaluated the efficacy, safety, and pharmacokinetics of a single subcutaneous pegfilgrastim injection with daily subcutaneous filgrastim administration in pediatric patients receiving myelosuppressive chemotherapy for sarcoma. PATIENTS AND METHODS Forty-four patients with previously untreated, biopsy-proven sarcoma stratified into three age groups (0-5, 6-11, and 12-21 years) were randomly assigned in a 6:1 randomization ratio to receive a single pegfilgrastim dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 36 publications
12
48
0
Order By: Relevance
“…Similarly, a phase 2 study of pediatric sarcoma patients showed that the safety and efficacy of pegfilgrastim 100 µg/kg was comparable to daily injections of filgrastim 5 µg/kg [63]. Pharmacokinetic profiles in pediatric patients were consistent with those in adult patients [63]. …”
Section: Selection Of the Optimal Pegfilgrastim Dose For Clinical Usementioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, a phase 2 study of pediatric sarcoma patients showed that the safety and efficacy of pegfilgrastim 100 µg/kg was comparable to daily injections of filgrastim 5 µg/kg [63]. Pharmacokinetic profiles in pediatric patients were consistent with those in adult patients [63]. …”
Section: Selection Of the Optimal Pegfilgrastim Dose For Clinical Usementioning
confidence: 82%
“…Subsequently, a phase 3 noninferiority study in breast cancer patients demonstrated that a single injection of pegfilgrastim 100 µg/kg per cycle was as safe and effective as multiple daily injections of filgrastim 5 µg/kg per cycle for reducing neutropenia and its complications [62]. Similarly, a phase 2 study of pediatric sarcoma patients showed that the safety and efficacy of pegfilgrastim 100 µg/kg was comparable to daily injections of filgrastim 5 µg/kg [63]. Pharmacokinetic profiles in pediatric patients were consistent with those in adult patients [63].…”
Section: Selection Of the Optimal Pegfilgrastim Dose For Clinical Usementioning
confidence: 99%
“…Dose-intensive CTH has become routine for the treatment of most pediatric sarcomas because CTH dose-intensity correlates with tumor response and outcome. Neutropenia is a common toxicity of these regimens (Ferrari et al, 2005;Grier J o u r n a l o f R a d i a t i o n R e s e a r c h a n d A p p l i e d S c i e n c e s 8 ( 2 0 1 5 ) 1 1 0 e1 1 9 et al, 2003;Spunt et al, 2010). Both the depth of the neutrophil nadir and duration of severe neutropenia influence the development of infectious complications.…”
Section: Discussionmentioning
confidence: 98%
“…Both the depth of the neutrophil nadir and duration of severe neutropenia influence the development of infectious complications. Therefore, preventing or shortening the duration of neutropenia following CTH may facilitate dose-intensity, improve safety, and control costs (Spunt et al, 2010). In the current study, Hematological toxicity was seen in all patients, 71.7% of them were neutropenic and develop febrile neutropenia (FN).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy, safety, and PK of a single 100-mg/kg subcutaneous dose of pegfilgrastim have been evaluated and compared to 5 mg/kg subcutaneous daily filgrastim in pediatric patients receiving myelosuppressive chemotherapy for sarcoma [49]. The maximum median pegfilgrastim concentration was achieved approximately 1-2 days after pegfilgrastim administration and was sustained until the ANC nadir was reached.…”
Section: Pharmacokinetics Of Pegfilgrastim In Neutropenic Pediatric Pmentioning
confidence: 99%